Jordan E-Government Challenges and Progresses - Al-Shboul, Muhannad Anwar; Alsmadi, Izzat (International Journal of Advanced Corporate Learning (iJAC), 2010)
For several years, Jordan has been working in building and improving its e-government infra structure. As a result, there have been some improvements in the position of Jordan e-government relative to the worldsâ?? e-governments (according to some reports). However, some metrics and statistics about the online users do not indicate that there is a large percent of Jordanian citizens who are using or utilizing e-government websites. This research tries to evaluate the progresses and weaknesses in those websites. It also focuses on the lack of local certificate authorities in Jordan as one of the major factors that is limiting the overall online business and activities in Jordan. There are few websites in Jordan that are certified (by international third parties). This forces those websites to outsource trust to third international parties. Digital certificates are one of the major required parts for building an infrastructure for the e-government in particular and the e-business in general.